PENINGKATAN KAPASITAS PERADILAN ADAT MAJELIS KUTAI DALAM PERLINDUNGAN HUTAN ADAT DESA LADANG PALEMBANG KECAMATAN LEBONG UTARA KABUPATEN LEBONG - M. Yamani; M. Abdi; Hamdani . (Universitas Bengkulu, 2017)
Local government of Ladang Palembang Lebong District has a specific way to managevillage forest and protected forest nearby the village area. Forests are set in theRegulation Village, Ladang Palembang Village Regulation No. 5 of 2009 on VillageProtected Forest, Indigenous Forest, and Green Area of Ladang Palembang. It containsmaterial laws that provide sanctions for any person who violates indigenous forests andprotected forests around the village of Ladang Palembang. However, to enforce the rulesof material law, Kutai assembly faces a lack of procedural law or formal written law thatcan be used as a guide in establishing the Ladang Palembang Village Regulation No. 5 of2009. Problem faced is a concern that skilled human resources are crisis to run Kutaiassembly, which threatens the sustainability of the Kutai assembly judicial system that hasbeen created. The method used in this society service activity is dialogical teaching, beginsfrom focused discussion, in-depth interviews, formulate a draft model of formal legal rulesof customary justice panel of Kutai, the regulation draft of the Ladang Palembang about Proceedings Technical Guidelines on Kutai Assembly Indigenous Justice of LadangPalembang, and testing or socialization. The result of the activities is drafting of formallaw model that governing the guide proceedings in the assembly Kutai, and the draft of theLadang Palembang Village Regulation on guidelines for resolution of cases of violationsinvolving indigenous forest of Ladang Palembang.Key words: forest, indigenous, local law, Kutai assembly